Effect of Experimental Factors in the Growth of Carbon Nanotubes from CO2 by MPECVD Process - Baldovino, Fritzie Hannah B.; Auresenia, Joseph L. (ASEAN Journal of Chemical Engineering, 2014)
The effects of experimental factors such as type of catalyst (nickel and cobalt) and substrate (iron and silicon wafer) in the growth of carbon nanotubes (CNT) from CO2 by microwave plasma-enhanced chemical vapor deposition (MPECVD) was systematically studied. Catalyst size and CNT grown were examined using scanning electron microscope (SEM). Furthermore, gas chromatography (GC) was used to analyze the effluent gas. Moreover, suitable type of catalyst and substrate were determined in terms on the amount of CNT grown, purity, and carbon conversion.